Pengembangan Sensor Ultrasoic Guna Pengukuran Pasang Surut Laut Secara Otomatis dan Real Time - Romi Fadly; Citra Dewi (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2019)
The bathymetric mapping activity at sea requires sea tide data for the needs of the depth of measurement results. This manual tidal observation is carried out day and night without stopping for a certain period of time, so that a minimum of 4 people are needed to observe one observation station. This manual observation is prone to reading errors, especially at night. Basically there are currently semi-automatic and automatic tidal gauges for sale, but the price is quite expensive. In this study, tide gauges have been developed automatically and real time both in observations and in data transmission using ultrasonic and micro-controller sensor technology. The method used is a design by utilizing an ultra-sonic sensor and micro controller arduino uno, as well as a GSM module (Global System for Mobile Communications). Each device is connected to a micro controller then programming is done for the data retrieval process, calculation of water level, and sending data to mobile phones through the SMS (Short Message Service) facility. Testing the results of tidal measurements from the tools made was carried out in the hydro-graphic laboratory and then tested directly into the field around the coast of Lampung bay. This study produces equipment for measuring tides automatically and real time with ultrasonic sensors. The results of tidal measurements will be stored in a micro SD and displayed on the LCD screen, and sent to the destination number via SMS with the SIM module 800L v.2. The error rate generated from the field test is 1.833%